2014
DOI: 10.1371/journal.pone.0106430
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Merkel Cell Polyomavirus in the General Rural Population of Anyang, China

Abstract: BackgroundDespite the probably causal link between Merkel cell polyomavirus (MCPyV) infection and Merkel cell carcinoma (MCC), a rare but aggressive skin malignancy, little is known about the seroepidemiology of MCPyV among healthy adults in China.MethodsSerum antibodies against MCPyV were evaluated by multiplex serology in a population-based study of 5548 adults (including 1587 heterosexual couples) aged 25–65 years who were enrolled from rural Anyang, China in 2007–2009. Univariate and multivariate logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 35 publications
(59 reference statements)
5
39
1
Order By: Relevance
“…MCPyV has a seroprevalence of approximately 80% in the healthy, adult population [13][14][15][16][17][18]. MCPyV is chronically shed from healthy skin [20], but can also cause an aggressive skin cancer known as Merkel cell carcinoma [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCPyV has a seroprevalence of approximately 80% in the healthy, adult population [13][14][15][16][17][18]. MCPyV is chronically shed from healthy skin [20], but can also cause an aggressive skin cancer known as Merkel cell carcinoma [1].…”
Section: Discussionmentioning
confidence: 99%
“…Serological studies demonstrated that seroprevalence against MCPyV increases with age, and reaches up to~80% in healthy individuals [13][14][15][16][17][18]. Little is known about the route of infection, transmission and the cell tropism of MCPyV.…”
Section: Introductionmentioning
confidence: 99%
“…Serum specimens and questionnaire data were collected from all participants (aged 25–65 years and without prior diagnosis of cancer, immunodeficiency disorders, cardiovascular illness or HBV/HCV/HIV) in six of the nine villages which were cluster-sampled in the baseline survey of a population-based oesophageal cancer cohort in rural Anyang, China, in 2007–2009 4 5. All participants provided written informed consent and the study protocol was approved by the Institutional Review Board of the School of Oncology, Peking University.…”
Section: Methodsmentioning
confidence: 99%
“…Serum antibodies to 10 HPV types were tested using a bead-based glutathione S-transferase (GST)-L1 multiplex serology assay, using a Bio-Plex 200 system (BIO-RAD, USA) 4 6. The median fluorescence intensity (MFI) values for each HPV antigen were calculated by subtracting the MFI for beads coated with GST alone.…”
Section: Methodsmentioning
confidence: 99%
“…35 Fortunately, although MCPyV is a common infection in the population, MCC remains rare with an estimated 3 cases occurring per million people. 29,36,37 Historically, the oncogenesis of MCC was poorly understood 32 ; however, the discovery by Feng et al, 30 which implicated MCPyV in the pathogenesis of MCC, has prompted significant scientific activity in this field. His group demonstrated that the virus was integrated into the genome of MCC specimens and approximately 66% to 80% of MCC specimens are positive for MCPyV.…”
Section: Introductionmentioning
confidence: 99%